Designing Interventions for Implementation in Schools: A Multimethod Investigation of Fidelity of a Self-Monitoring Intervention. Issue 1 (27th December 2020) - Holmes, Shannon R.; Thompson, Aaron M.; Herman, Keith C.; Reinke, Wendy M.
Abstract: Interventions for youth are often studied in school settings, yet there are barriers that hinder schools from actively participating in the research studies. To ensure interventions are studied in the context they are intended for, adopted in a timely manner, and regularly used in practice as designed, researchers can conduct studies in a manner that reflects the dynamic needs of schools. Participatory action research, which engages participants in the research process, and coproduction of interventions, which involves end users in the development of interventions, are complementary frameworks that may increase the utility and flexibility of school-based interventions while also improving engagement and fidelity of intervention implementation. This study explored the implementation of a self-monitoring intervention, Self-Management And Regulation Training Strategy (SMARTS), developed using these approaches. Using multiple methods, findings indicate that school counselors (i.e., natural treatment agents) valued helping in the development of SMARTS and were able to implement it in school settings with fidelity. In fact, the quality with which they implemented components of the intervention was significantly related to students' engagement in intervention procedures. Implications and limitations are discussed.